2021
DOI: 10.1016/j.amsu.2021.102872
|View full text |Cite
|
Sign up to set email alerts
|

Exercise adaptations and TGF-β1 levels in recreational cyclists

Abstract: Background Cycling is a physical exercise that is widely performed to improve physical fitness. Regular physical exercise will lead to adaptations to exercise. This adaptation is useful in suppressing the production of reactive oxygen stress (ROS) generated in response to cellular metabolism that uses oxygen. Transforming growth factor beta-1 (TGF-β1) plays a role in increasing the production of ROS, thus, when the concentration is low, it would lead to an improvement in physical fitness. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…They observed that the level of TGF-β1 was lower in the recreational cyclist than in the sedentary control group. Several other studies have confirmed that participating in moderate regular exercise would reduce the level of circulating TGF-β in both human and rodents [ 49 - 51 ].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…They observed that the level of TGF-β1 was lower in the recreational cyclist than in the sedentary control group. Several other studies have confirmed that participating in moderate regular exercise would reduce the level of circulating TGF-β in both human and rodents [ 49 - 51 ].…”
Section: Resultsmentioning
confidence: 93%
“…They observed that 8 min/d (moderate) swimming decreased TGF-β1 levels both in serum and liver cancer tissues. In humans, a study compared the level of TGF-β1 in the regular cyclist (2–3 times a week, average 30–60 min each) with sedentary control [ 49 ]. They observed that the level of TGF-β1 was lower in the recreational cyclist than in the sedentary control group.…”
Section: Resultsmentioning
confidence: 99%
“…The context in which this influence is explored and the timing after the PE could explain some of this variability. Regarding TGF-β, a key cytokine for tissue remodeling, given the context PE can either increase [ 57 , 58 , 59 ] or decrease [ 60 , 61 , 62 ] its production.…”
Section: Discussionmentioning
confidence: 99%
“…Because ROS are produced more frequently when TGF-beta-1 (TGF-β1) is present in low concentrations, this would result in increased fitness. Consistent exercise starts a process of adaptation that makes antioxidant enzymes work harder to prevent TGF-β1 activation [ 82 ]. TGF-β1 and bone morphogenic protein (BMP) signaling are also crucial for chondrogenic and osteogenic differentiation.…”
Section: Interconnected Bone and Muscle Molecular Pathwaysmentioning
confidence: 99%